2016
DOI: 10.1002/cjoc.201600231
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in the Application of Polyoxometalates for Dye‐sensitized/Organic Solar Cells

Abstract: At present, high efficiency and low fabrication cost are still the main goal that people pursuit for next‐generation solar cells such as dye‐sensitized solar cells (DSSCs) and organic solar cells (OPVs). Polyoxometalates (POMs), as an environmentally friendly material, are a type of stable, low cost and soluble oxide clusters with desirable features, including highly tunable structural properties, peculiar optoelectronic properties and excellent redox properties. Thus, during the recent years, POMs have been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…Polyoxometalate-based metal–organic frameworks (POMOFs) are a class of emerging supramolecular hybrids that combine the functionalization properties of metal–organic frameworks (MOFs) with the rich physicochemical properties of polyoxometalates (POMs). On one hand, MOF research has seen an unprecedented growth in the last two decades and encompassed many other secondary research fields primarily due to their functionalized porous properties and applications in gas storage, magnetism, photochemistry, proton conduction, and catalysis. , POMs, on the other hand, are nanoclusters of early transition-metal (TM) oxides, having high anionic charge and oxygen-rich surface with a wide variety of sizes, compositions, and structures. , Chemistry of TMs, anionic nature, and surface oxygen renders POMs as highly active materials for catalysis, electrochemical applications, and rich photochemistry. The rich redox chemistry of TMs incorporated into the rigid but chemically flexible nanoframework of POMs have found wide applications in the field of energy storage, photo- and electrocatalysis, organic catalysis, solar cells, supercapacitors, nonlinear optics, etc. The hierarchical structures of the POMOFs fine-tune the structural and electronic properties of the multifunctional hybrids and play a crucial role in determining their applications and efficiencies . Synthesis and design of hierarchical assemblies like zero-dimensional (0D) open frameworks, one-dimensional (1D) chains, and two-dimensional (2D) nets, based on primary and secondary building units of basic MOF architectures and POMs, have started a new era of novel material design for targeted use in various fields ranging from material science to biomedicine.…”
Section: Introductionmentioning
confidence: 99%
“…Polyoxometalate-based metal–organic frameworks (POMOFs) are a class of emerging supramolecular hybrids that combine the functionalization properties of metal–organic frameworks (MOFs) with the rich physicochemical properties of polyoxometalates (POMs). On one hand, MOF research has seen an unprecedented growth in the last two decades and encompassed many other secondary research fields primarily due to their functionalized porous properties and applications in gas storage, magnetism, photochemistry, proton conduction, and catalysis. , POMs, on the other hand, are nanoclusters of early transition-metal (TM) oxides, having high anionic charge and oxygen-rich surface with a wide variety of sizes, compositions, and structures. , Chemistry of TMs, anionic nature, and surface oxygen renders POMs as highly active materials for catalysis, electrochemical applications, and rich photochemistry. The rich redox chemistry of TMs incorporated into the rigid but chemically flexible nanoframework of POMs have found wide applications in the field of energy storage, photo- and electrocatalysis, organic catalysis, solar cells, supercapacitors, nonlinear optics, etc. The hierarchical structures of the POMOFs fine-tune the structural and electronic properties of the multifunctional hybrids and play a crucial role in determining their applications and efficiencies . Synthesis and design of hierarchical assemblies like zero-dimensional (0D) open frameworks, one-dimensional (1D) chains, and two-dimensional (2D) nets, based on primary and secondary building units of basic MOF architectures and POMs, have started a new era of novel material design for targeted use in various fields ranging from material science to biomedicine.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the small molecular solar cells demonstrated many prominent advantages compared with polymer solar cells, in terms of ease of purification, discrete molecular weight, small batch-to-batch variation, and high open-circuit voltage (V oc ). [26][27][28][29][30][31][32][33][34][35] However, the relatively low viscosity requires the incorporation of polymers such as polystyrene (PS), polydimethylsilicone (PDMS), conjugated polymers, and so on, to improve the processing conditions. [36][37][38][39][40] Whether the polymers enhance or restrict the crystallization of donor molecules is still under debate, depending on the type of small molecules and polymers.…”
Section: Introductionmentioning
confidence: 99%
“…[5] However,l ow electron mobility,m ismatchedb and gaps, and the high-traps tate density of pristine TiO 2 usually lead to some deteriorative influence on the device efficiency, stability, or notorious hysteresis of PSCs. [23] In High quality electron-transport layer (ETL) with superior optical and electrical properties is an essential part in high efficient perovskite solar cells (PSCs). Accordingly,m any efforts have already been devoted to modifying and manipulatingp ristine TiO 2 by doping with metal or nonmetal (such as Mg, Al, and Nd), regulating the morphology and crystallinity of TiO 2 (such as nanorods, nanotubes, or rutile phase) and interface engineering of TiO 2 film [bis(trifluoromethane)sulfonimide lithium salt (LiTFSI) or PCBM treatment].…”
Section: Introductionmentioning
confidence: 99%
“…Notably,T iO 2 modified with POM composites have been widely utilized as photoanodes in DSSCs, which can dramatically accelerate the photogenerated electron-transport rate, increase electron-injection efficiency,a nd retard charge-carrier recombination compared to the pristine TiO 2 -based photoanode. [23] In High quality electron-transport layer (ETL) with superior optical and electrical properties is an essential part in high efficient perovskite solar cells (PSCs). In this work, SiW 12 -TiO 2 mesoporousf ilm is prepared by af acile one-step spin-coating deposition method and successfully applied as ETL in PSCs.…”
Section: Introductionmentioning
confidence: 99%